2016
DOI: 10.1111/1365-2435.12795
|View full text |Cite
|
Sign up to set email alerts
|

Lizards paid a greater opportunity cost to thermoregulate in a less heterogeneous environment

Abstract: Summary The theory of thermoregulation has developed slowly, hampering efforts to predict how individuals can buffer climate change through behaviour. Mixed results of field and laboratory experiments underscore the need to test hypotheses about thermoregulation explicitly, while measuring costs and benefits in different thermal landscapes. We simulated body temperature and energy expenditure of a virtual lizard that either thermoregulates optimally or thermoconforms in a landscape of either low or high qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 52 publications
3
74
0
Order By: Relevance
“…Therefore, urban habitats are more favorable for A. sagrei , which may have trouble persisting in more close‐canopied sites, such as forested habitats, that restrict their ability to achieve higher body temperatures. It is important to note that while costs of thermoregulation may be lower in urban sites, Basson, Levy, Angilletta, and Clusella‐Trullas () showed that even in a low‐quality thermal habitat with high thermoregulatory costs in the laboratory, Cordylus lizards prioritized maintaining T b within T pref . It may be necessary to maintain warmer body temperatures that confer higher activity in urban habitats in the Miami area, even if costly, to successfully compete with multiple other introduced and native anoles (Kolbe et al, ), or manage urban predation pressure (Chejanovski, Avilés‐Rodríguez, Lapiedra, Preisser, & Kolbe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, urban habitats are more favorable for A. sagrei , which may have trouble persisting in more close‐canopied sites, such as forested habitats, that restrict their ability to achieve higher body temperatures. It is important to note that while costs of thermoregulation may be lower in urban sites, Basson, Levy, Angilletta, and Clusella‐Trullas () showed that even in a low‐quality thermal habitat with high thermoregulatory costs in the laboratory, Cordylus lizards prioritized maintaining T b within T pref . It may be necessary to maintain warmer body temperatures that confer higher activity in urban habitats in the Miami area, even if costly, to successfully compete with multiple other introduced and native anoles (Kolbe et al, ), or manage urban predation pressure (Chejanovski, Avilés‐Rodríguez, Lapiedra, Preisser, & Kolbe, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such results were found in bearded dragons, where animals were examined in several types of thermal arenas and found to lose thermoregulatory precision only in the arena with very high variability (Cadena & Tattersall, ). Similarly, for lizard species in more‐complex arenas, patch dispersion that requires greater locomotion leads to reduced accuracy in thermoregulation (Sears et al ., ; Basson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the structure and complexity of the thermal landscape likely plays a role in thermoregulatory performance (Basson et al . ; Sears et al . ), with more complex environments potentially ameliorating the negative thermoregulatory effects of competition.…”
Section: Discussionmentioning
confidence: 99%